Making Of Asian America : Through Political Participation - Lien, Pei-te, 1957- (Book collections on Project MUSE., 2001)
Asian Americans are widely believed to be passive and compliant participants in the U.S. political process-if they participate at all. In this book, Pei-te Lien maps the actions and strategies of Asian Americans as they negotiate a space in the American political arena. Professor Lien looks at political participation by Asian Americans prior to 1965 and then examines, at both organizational and mass politics levels, how race, ethnicity, and transnationalism help to construct a complex American electorate. She looks not only at rates of participation among Asian Americans as compared with blacks, Latinos, American Indians, and non-Hispanic whites, but also among specific groups of Asian Americans-Chinese, Japanese, Filipinos, Koreans, Asian Indians, and Vietnamese. She also discusses how gender, socioeconomic class, and place of birth affect political participation. With documentation ranging from historical narrative to opinion survey data, Professor Lien creates a picture of a diverse group of politically active people who are intent on carving out a place for themselves in American political life.